2006
DOI: 10.5713/ajas.2006.1671
|View full text |Cite
|
Sign up to set email alerts
|

Correlations between Heterozygosity at Microsatellite Loci, Mean d2 and Body Weight in a Chinese Native Chicken

Abstract: A total of two hundred twenty eight half-sib chickens were scored for allele size at 20 microsatellite loci to estimate individual heterozygosity and mean d 2 . The averages of microsatellite heterozygosity, allele per locus and mean d 2 were 0.39, 3.6 and 49, respectively. The body weight was measured biweekly from birth to twelve weeks of age. Gompertz function was assumed to simulate body weight and to estimate the growth model parameters. Due to sex effect on body weight, the regression of body weight on h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
1
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
(43 reference statements)
2
9
1
4
Order By: Relevance
“…Zhang et al (2005) reported that MLH, not MD2, correlated with neonatal weight in a crossbreeding F1 pig population. Similarly, there were positive correlations between MLH and neonatal weight for both sexes of a native breed of Chinese chicken, but this was not the case for MD2 (Liu et al 2006). In contrast to domestic animals, such correlation is hardly detectable in wild populations, because environmental factors, such as disease, climate, and mother's condition, may also affect fitness-related traits.…”
Section: Individual's Genetic Diversity and Neonatal Weightmentioning
confidence: 63%
See 1 more Smart Citation
“…Zhang et al (2005) reported that MLH, not MD2, correlated with neonatal weight in a crossbreeding F1 pig population. Similarly, there were positive correlations between MLH and neonatal weight for both sexes of a native breed of Chinese chicken, but this was not the case for MD2 (Liu et al 2006). In contrast to domestic animals, such correlation is hardly detectable in wild populations, because environmental factors, such as disease, climate, and mother's condition, may also affect fitness-related traits.…”
Section: Individual's Genetic Diversity and Neonatal Weightmentioning
confidence: 63%
“…In domestic animals, positive correlations between individual heterozygosity and neonatal weight were demonstrated (Zhang et al 2005;Liu et al 2006). Zhang et al (2005) reported that MLH, not MD2, correlated with neonatal weight in a crossbreeding F1 pig population.…”
Section: Individual's Genetic Diversity and Neonatal Weightmentioning
confidence: 94%
“…Що стосується індивідуальних оцінок мультилокусної гетерозиготності (MLH) та оцінок міри mean d 2 за локусами МС-ДНК серед свиноматок ВБП з обох господарств, то, в цілому, особини СГПП "Техмет-Юг" характеризувалися більш низьким рівнем генетичної мінливості, але вірогідні відмінності було встановлено лише у відношенні міри mean d 2 (непараметричний тест Манна-Уітні: P < 0,05). В переважній більшості робіт, що розглядали вплив різних оцінок гетерозиготності (коефіцієнт інбридингу, гетерозиготність та оцінки міри d 2 як для окремих структурних генів та локусів МС-ДНК, так й їх мультилокусна оцінка) на ознаки тварин, що розводяться в штучних умовах -риб (Appleyard et al, 2001), хутрових звірів (Kashtanov et al, 2003), курей (Liu et al, 2006) та качок (Agatep, 2015), свиней (Wu et al, 2001;Liu et al, 2003;Jiang et al, 2005;Zhang et al, 2005;Iversen et al, 2019), кіз (Han et al, 2013), коней (Curik et al, 2003;Luís et al, 2007), домашніх овець (Smith et al, 2012;Valilou et al, 2016), яків (Jiang et al, 2004) та свійської худоби (Driscoll et al, 2011) -найчастіше відмічалось переважання гетерозиготних особин над гомозиготними. Хоча у випадку тилапії було встановлено, що особини, гомозиготні за локусом UNH146, переважали гетерозигот за довжиною та масою тіла (Appleyard et al, 2001).…”
Section: результатиunclassified
“…Хоча негативні наслідки інбридингу та зниження гетерозиготності на відтворювальні якості та виживаність у популяціях диких тварин вже добре вивчено, відомо небагато досліджень щодо їх впливу на ознаки продуктивності у свійських і сільськогосподарських тварин. Протягом останніх 20 років з'явилася низка публікацій, що розглядають вплив різних оцінок гетерозиготності (коефіцієнт інбридингу, гетерозиготність та міра d 2 як для окремих структурних генів і локусів МС-ДНК, так й їх мультилокусна оцінка) на ознаки тварин, що розводяться в штучних умовах -риб (Appleyard et al, 2001), хутрових звірів (Kashtanov et al, 2003), курей (Liu et al, 2006), качок (Agatep, 2015), свиней (Wu et al, 2001;Liu et al, 2003;Jiang et al, 2005;Zhang et al, 2005;Iversen et al, 2019), кіз (Han et al, 2013), коней (Curik et al, 2003;Luís et al, 2007), домашніх овець (Smith et a., 2012;Valilou et al, 2016), яків (Jiang et al, 2004) та свійської худоби (Driscoll et al, 2011).…”
Section: вступunclassified